The effect of risk management committee characteristics and risk-taking among Islamic financial institutions in Bangladesh / Md. Mohidul Islam … [et al.] - Islam, Md. Mohidul; Bhuiyan, Abul Bashar; Md Kassim, Aza Azlina; Rasli, Salina (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The purpose of the study is to examine the influences of Risk Management Committee (RMC) characteristics on risk taking of the Islamic Financial Institutions of (IFIs) in Bangladesh. The study conducts dynamic strongly panel data regarding annual report of quated14 IFIs in Bangladesh during the period 2013-2018. Particularly the study has conducted the first and second lag of dependent variables and applied under GMM model in Stata software. The findings of the study indicates that, hypothesis result of Risk Management Committee characteristics is negative significant that means RMC is essential to reduce risk taking of IFIs in Bangladesh. The study provide support for financial expertise to put in right place to reduce excess risk taking that could be a valuable source of knowledge for reducing risk taking to risk committee.